Problematika Guru Dalam Mengevaluasi Pembelajaran Seni Budaya Di Sekolah Menengah Pertama Negeri Di Kota Mataram - Wulandari, Ni Putu; Andari, Ida Ayu Made Yuni (Widya Sundaram : Jurnal Pendidikan Seni Dan Budaya, 2025)
This research explores and analyses the challenges cultural arts teachers at SMP Negeri Mataram City face in implementing learning evaluation using the competency-based curriculum. The expected cultural arts evaluation includes assessing student's creative process, attitude, knowledge, and skills, but most teachers still rely on product-based assessment. The method was qualitative, collecting data through questionnaires, interviews, and observations of 15 cultural arts teachers at SMP Negeri Kota Mataram. The results showed that teachers face difficulties in designing evaluation instruments according to the curriculum, especially due to the lack of understanding of authentic evaluation and time constraints due to high administrative loads. This study also found that the use of technology in evaluating cultural arts learning is still very limited. This research provides important insights into the need for competency-based evaluation training for cultural arts teachers and the utilisation of technology in the evaluation process. The findings form the basis for developing more effective training strategies to improve school cultural arts evaluation practices.